PHYSICAL STABILITY TEST FORMULA ON SOYBEAN SEEDS EXTRACT (GLYCINR MAX L.) GROBOGAN REGENCY IN GEL - Gigih Kenanga Sari; Anita Dwi Septiarini; Katharina Anrina (Joseph: Journal of Science and Pharmacy, 2021)
Background: Soybean (Glycine max L.) is one of the leading food commodities in Grobogan Regency. Soybean belongs to the   flavonoid group, which is one of the natural antioxidant-producing   foodstuffs. One of the important components / bioactive compounds   found in soybeans and acts as an antioxidant is isoflavones.   Isoflavones contained in soybean extract are non-toxic to human   skin and can provide a protective effect from the sun, so it can be   said that the isoflavones contained in soybean extract can have the   ability to scavenge free radicals as well as act as a skin protector   from the sun. To obtain a protective effect against ultraviolet light,   an appropriate dosage form should be selected, which does not   cause irritation, and can carry medicinal ingredients well. Gel   preparations have several advantages including non-sticky, easy to   dry, has a thin film layer so that it is easy to wash. Purpose: This   study was to produce a gel preparation and to determine the physical stability of the Soybean (Glycine max L.) Seed Extract Formulation in Grobogan Regency in Gel Preparations. Method: The instrument uses analytical balance, measuring cup, object glass, stirring rod, mortar and stamper, pH stick, viscometer, stopwatch, adhesion test equipment, dispersion test equipment, and freeze dry. The ingredients are Grobogan soybean seed dry extract, HPMC, methylparaben, propylparaben, glycerin, and distilled water. Results: This research resulted in a gel preparation with soybean seed extract as the raw material. The gel produced when the concentration of HPMC was doubled, from a concentration of 5% to 10% and from a concentration of 10% to 20% could increase viscosity, stickiness, and decrease dispersion, but the increase in HPMC concentration did not affect the pH of the preparation. Conclusion: This study resulted in a gel preparation with an increase in concentration and the gel can affect the physical stability of the gel as indicated by the increase in viscosity, gel adhesion, and a decrease in gel dispersion, but the increase in HPMC concentration did not affect the pH of the preparation